2021
DOI: 10.1038/s41598-021-95782-1
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor imaging of calcium-binding proteins in human kidney stones for elucidating the effects of proteins on crystal growth

Abstract: The pathogenesis of kidney stone formation includes multi-step processes involving complex interactions between mineral components and protein matrix. Calcium-binding proteins in kidney stones have great influences on the stone formation. The spatial distributions of these proteins in kidney stones are essential for evaluating the in vivo effects of proteins on the stone formation, although the actual distribution of these proteins is still unclear. We reveal micro-scale distributions of three different protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 53 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…After the COM crystals form, they can grow continuously under the supersaturated condition by adding free Ca 2+ and C 2 O 4 2− ions to the crystals [ 61 ]. Immunofluorescence staining has revealed the spatial distribution of negatively charged proteins inside and outside of the crystals during growing process [ 19 ]. In our present study, negatively charged FL-HSP90, N-HSP90 and C-HSP90, and positively charged M-HSP90 could enhance the growth of COM crystals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the COM crystals form, they can grow continuously under the supersaturated condition by adding free Ca 2+ and C 2 O 4 2− ions to the crystals [ 61 ]. Immunofluorescence staining has revealed the spatial distribution of negatively charged proteins inside and outside of the crystals during growing process [ 19 ]. In our present study, negatively charged FL-HSP90, N-HSP90 and C-HSP90, and positively charged M-HSP90 could enhance the growth of COM crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, alterations of protein expression in renal tubular epithelial cells (RTECs) by COM crystals have been identified via proteomics approach [ 8 17 ]. Interestingly, functional analyses have demonstrated that some of such altered proteins play roles as modulators (promoters or inhibitors) [ 18 , 19 ] and COM crystal receptors [ 20 22 ] during the stone-forming processes.…”
Section: Introductionmentioning
confidence: 99%
“…The final structure of kidney stones and/or phase transformation speed estimated from the structure suggests the history of kidney stone growth and urine environment changes. Combined with our recent technique, multicolor imaging of calcium-binding proteins in human kidney stones [9], we can evaluate various kidney stone samples, and the information that stones have will reveal the factors of the stone formation processes and the interaction with organic molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism of CaOx in vivo is crucial for understanding the stone formation process. Further investigation using quantitative measurement procedures of CaOx combined with the visualization of multiple proteins in human kidney stones [9] will elucidate the kidney stone formation processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation